Вплив банківської системи на економіку країни - Капраль, О. Р. (Видавництво Львівської політехніки, 2017)
Досліджено вплив банківської системи на розвиток економіки країни. Проаналізовано макроекономічну ситуацію у банківській системі та визначено низку зовнішніх та внутрішніх загроз. Оцінено вплив банківської системи на економіку країни і доведено, що стабільність та ефективність банківської системи залежать від стану економіки країни.

The impact of the banking system on the country’s economy in the article is studied. The analysis of the macroeconomic situation in the banking system is conducted and a range of external and internal threats is identified. The effect of the banking system is evaluated and the dependence of stability and efficiency of the banking system upon the economy is proved. The banking system of the country is an organic part of the overall economical complex and directly interacting with all areas of the economy, has a significant influence on economical processes. That occurs in the formation of an optimal environment for mobilization and free transfusion of financial resources, for the accumulation of funds for restructuring of the economy and its integration into the global economy. The stability and the efficiency of the banking system depends on the economy. Approved reforms of the banking system and the NBU should stabilize the main elements of the economic system of the country, ensure the economic security of the real economy and remove restrictions that block the necessary of its qualitative and quantitative changes.
Effect of the banking system on the economy
Keywords: економіка країни; банківська система країни; макроекономічна ситуація у банківській системі; the economy; the banking system of the country; the macroeconomic situation in the banking system; 629; 6 58